The Effectiveness of Inquiry and Practice During Project Design Courses at a Technology University - Fan, Jing-Yun; Ye, Jian-Hong (Frontiers in Psychology, 2022)
Among the many teaching methods, inquiry-based teaching is considered to be an effective way for students to learn and solve problems on their own. However, most of the research related to inquiry-based teaching and learning has concentrated mainly on K-12 education, while few to no studies have focused on the application of inquiry-based teaching and learning in project design courses at university level. Therefore, in order to expand the understanding of the application effect of inquiry-based teaching at university level, this study adopted the quasi-experimental design method, and through the purposive sampling method, 20 students from the Department of Fashion Design at a University of Science and Technology were invited to participate in this study. During the 9-month period, teaching experiments were carried out using two inquiry models, QC/ADEAC and QD/ODEAC. First, when participants were thinking of a creative topic, they followed the process: Question (Q), Collection/Analysis (C/A), Discussion (D), Explanation (E), Amendment (A), and Confirmation (C) in the course. During the production process, the participants were allowed to improve on their work through the process of Question (Q), Doing/Observation (D/O), Discussion (D), Explanation (E), Amendment (A), and Confirmation (C). The teacher became a true guide, so that the participants could explore and work out how to improve their designs through independent inquiry and practice. In this study, questionnaires were administered to participants at five important stages of the design project: “theme development,” “color development,” “first Work,” “second Work,” and “third Work.” The results of the five surveys showed that the participants’ curriculum interest, curriculum value perception, and curriculum confidence in the inquiry program all increased.